The evolving large-strain shear responses of progressively osteoarthritic human cartilage. Issue 5 (May 2019) - Maier, F.; Lewis, C.G.; Pierce, D.M.
Summary: Objective: The composition and structure of articular cartilage evolves during the development and progression of osteoarthritis (OA) resulting in changing mechanical responses. We aimed to assess the evolution of the intrinsic, large-strain mechanics of human articular cartilage–governed by collagen and proteoglycan and their interactions–during the progression of OA. Design: We completed quasi-static, large-strain shear tests on 64 specimens from ten donors undergoing total knee arthroplasty (TKA), and quantified the corresponding state of OA (OARSI grade), structural integrity (PLM score), and composition (glycosaminoglycan and collagen content). Results: We observed nonlinear stress–strain relationships with distinct hystereses for all magnitudes of applied strain where stiffnesses, nonlinearities, and hystereses all reduced as OA advanced. We found a reduction in energy dissipation density up to 80% in severely degenerated (OARSI grade 4, OA-4) vs normal (OA-1) cartilage, and more importantly, we found that even cartilage with a normal appearance in structure and composition (OA-1) dissipated 50% less energy than healthy (control) load-bearing cartilage (HL0 ). Changes in stresses and stiffnesses were in general less pronounced and did not allow us to distinguish between healthy load-bearing controls and very early-stage OA (OA-1), or to distinguish consistently among different levels of degeneration, i.e., OARSI grades. Conclusions: Our results suggest that reductions in energy dissipation density can be detected by bulk-tissue testing, and that these reductions precede visible signs of degeneration. We highlight the potential of energy dissipation, as opposed to stress- or stiffness-based measures, as a marker to diagnose early-stage OA.